Improving Electric Powered UAVs' Endurance by Incorporating Battery Dumping Concept. (2015) - Chang, Tan; Yu, Hu
Abstract: Most studies concerning electric powered UAVs' performance are based on fixed-weight plane model for the fact that battery's weight remains unchanged during discharging. However, it is possible to extend electric powered UAVs' endurance by dumping exhausted batteries out of the aircraft in flight. Impact factors affecting the endurance performance of UAV with battery-dumping capability such as the battery dumping system (BDS) weight ratio, battery mounting and dumping device (BMDD) weight ratio, battery packs count and battery dumping strategy were studied and discussed. The optimum endurance with conventional fixed-weight model and battery dumping concept were then obtained and compared utilizing Genetic Algorithm